The Effect of Good University Governance on Management Performance: A Literature Review - Herny Nurhayati; Nurmala Ahmar Nurmala Ahmar (Al-Makki Publisher, 2022)
Governance is becoming increasingly important in universities as it is in the wider world of commerce and banking.Historically,universities were run by their academic communities,but as mass higher education has taken root,because university research has become an important element in the national economy and because the demand for better accountability in financial and academic performance has grown.The purpose of this study was to analyze the relationship between Good University Governance and Management Performance.This study was conducted through a literature review.The literature search was conducted using several electronic databases such as Google Scholar, Scopus, ProQuest,ScienceDirect,ACM Digital Library,by entering the keyword “Good University Governance” and “Management Performance”.